GREEN SYNTHESIS OF FE3O4 NANOMAGNETICS WITH MATOA LEAF EXTRACT (Pometia pinnata) AND ANTI-BACTERIAL ACTIVITY TEST AGAINST Staphylococcus Aureus AND Escherichia Coli - Sri Hartika; Poedji Loekitowati Hariani; Hermansyah Hermansyah (Jurusan Kimia FMIPA Universitas Lampung, 2024)
The aim of this research is to synthesize nanomagnetic Fe3O4 using matoa (Pometia Pinnata) leaf extract and test its antibacterial properties against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). The resulting nanomagnets were characterized using a Vibrating Sample Magnetometer (VSM) to determine magnetic properties, phase type, and crystal size using X-ray diffraction (XRD), morphology, and element composition using Scanning Electron Dispersive X-ray Spectroscopy (SEM-EDX) and functional group using Fourier Transform Infra Red (FTIR). Furthermore, the Fe3O4 obtained was tested for antibacterial activity against Gram-Positive and Gram-negative bacteria, namely S. aureus and E. coli. Characterization results show that the average crystal size of Fe3O4 is 12.07 nm and has magnetic properties of 68.01 emu/g, morphology shows that it forms aggregates of unequal sizes. FTIR characterization results show the presence of -OH, -CH, C=C, H-C-H, C-O, and Fe-O groups. The results of the anti-bacterial Fe3O4 test were able to inhibit S. aureus and E. coli bacteria at a concentration of 5000 ppm with an inhibitory zone diameter of 11,0 mm and 10,5 mm respectively. These results show that the nanomagnetic compound Fe3O4 has antibacterial activity.